POLA KEBERAGAMAAN MASYARAKAT MARGINAL - Ahmad Muttaqin (IAIN Purwokerto, 2015)
Abstract: This study examines the issue of the sociology of religion at the religious practices of local communities. Kampung Laut selected as a test site for two (2) major consideration. First, the practice of religion in the fom of ritual in Kampung Laut is different from the mainstream that is considered wrong and become targets for streamlining activities. Second, the typical characteristics of Kampung Laut people in the vortex of conflict govemment agencies on claims of ownership of natural resources. Correctional Institution (LP) as part of Kemenkumham, Cilacap regency govemment and PT. Perhutani conflict over land ownership arising from sedimentation along Segara Anak. Conflicts that exist tend to be maintained to a certain political interests. Even more, these institutions construct public issue by positioning Kampung Laut as threatening communities via label illegal loggers and destroyers of ecosystems. Bad image fomed through a process of marginalization is then formed the distinctive character of the community as a community of Kampung Laut resistant and latent. The method used in this research is descriptive qualitative sociological approach. Through sociological analysis, practice different religious rituals that seem to have rationalization based on the theory of action Weber in the category of value-oriented rationality. Different actions with mainstream thought to have more benefits in the context of the struggle for existence of identity in the practice of marginalization carried out by institutions conflictual. Religiorn becomes the entry point of this issue given its massive, communal, and mobilized by the transcendental values. Keywords: Religion, Conflict, Ritual, Mainstream.